PENDEKATAN MINDFULNESS UNTUK MENINGKATKAN PSYCHOLOGICAL WELL-BEING PADA SISWA SEKOLAH DASAR: SEBUAH SYSTEMATIC REVIEW - Kristina Betty Artati; Eka Wahyuni (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Backgrounds: Mindfulness interventions with various methods are currently being widely researched and proven to be effective for increasing psychological well-being for elementary school students. Objectives: The purpose of this article is to systematically review some of the results from the recent study that intervenes in mindfulness techniques to increase psychological well-being in elementary school students. Methods: The studies were carried out in several electronic databases within the past 7 years which were published in English. Conclusion: The study results left 12 journals that met the criteria. Mindfulness intervention for students aged 7-12 years with psychological problems in elementary school students. Mindfulness techniques are effective for reducing emotional dysregulation, increasing social skills, increasing happiness, quality of awareness, increasing concentration, increasing selective attention, improving mental health, increasing self-efficacy. Mindfulness technique training programs can be recommended for implementation in elementary schools and integrated into school curriculum programs.